The Utilization of Ternate Oral Tradition for The Identification of Potential Disasters - Rahma Do Subuh; Ramis Rauf; Farida Maricar; Afriani Ulya (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2024)
Oral traditions, as an integral part of a society's belief system, not only serve as a guide for society in daily life, such as interactions between members of society and other people, and even with nature or the environment, but they also serve as recorders of history and culture, including natural events. This paper aims to describe the oral traditions of Ternate to identify potential natural disasters that hit Ternate City in particular and North Maluku in general. Therefore, the author uses the theory of myth function to embody the main research problem. The approach used in this paper is semiotics, especially in interpreting natural disasters that occurred in the past through codes contained in oral stories or legends. The research results show that the people of Ternate can only explain a few natural events in the past. Then, it is ontologically digested into myth to symbolise the cosmic-mystical realm of thought. Apart from that, the results of this reflection are related to cause-and-effect events, give rise to rules of behaviour, and become local intellectual ideals. However, records of natural phenomena or past events in myths or legends can, in theory, be linked to the truth and thus make cycles of disaster predictable. On the other hand, in a formal educational setting, this legend can be used to teach about mitigation. Legends about the mysterious origins of certain lakes are thought to include aspects of disaster or mitigation in Ternate.